The Effectiveness of Communicative Language Teaching (ClT) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The article gives data about the general understanding of communicative language teaching, methods of applying them into teaching process and the productivity of CLT is discussed. Additionally, key benefits of CLT are presented in the paper.